2021
DOI: 10.3390/v13050817
|View full text |Cite
|
Sign up to set email alerts
|

HCMV Antivirals and Strategies to Target the Latent Reservoir

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous human herpesvirus. In healthy people, primary infection is generally asymptomatic, and the virus can go on to establish lifelong latency in cells of the myeloid lineage. However, HCMV often causes severe disease in the immunosuppressed: transplant recipients and people living with AIDS, and also in the immunonaive foetus. At present, there are several antiviral drugs licensed to control HCMV disease. However, these are all faced with problems of poor bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 133 publications
0
27
0
Order By: Relevance
“…Treatments are also under the continuous threat of the emergence of viral drug resistance or vaccine escape mutations. Hence, the identification of novel antiherpesviral drugs and targeting strategies remains a global research focus ( 10 , 11 ).…”
mentioning
confidence: 99%
“…Treatments are also under the continuous threat of the emergence of viral drug resistance or vaccine escape mutations. Hence, the identification of novel antiherpesviral drugs and targeting strategies remains a global research focus ( 10 , 11 ).…”
mentioning
confidence: 99%
“…It was showed that GCV inhibits EBV; HHV 6, 7, and 8; and hepatitis B virus (HBV) replication, as well. In the clinical practice, it is the drug of choice to treat the CMV infection [ 50 , 51 , 52 , 53 , 54 , 55 ]. GCV is indicated to treat cytomegalovirus retinitis as a suppressive therapy, used for the prevention of CMV disease in transplant recipients.…”
Section: Antiviral Drugsmentioning
confidence: 99%
“…GCV is first phosphorylated by the viral protein kinase (encoded by the CMV UL97 gene) and then diphosphorylated by cellular kinases. GCV is an inhibitor of viral DNA polymerase (encoded by the CMV UL54 gene) [ 18 , 50 , 51 ]. When orally administered, it is absorbed in only 5–10%.…”
Section: Antiviral Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, HCMV infection is the most frequent cause of congenital malformation in developed countries [ 147 ]. Although nucleoside analogues have been successfully used against HCMV, their use is hampered by the occurrence of serious side effects, the rapid emergence of resistance and the fact that their efficacy is limited to alleviating symptoms, without eradicating the latent infection [ 148 , 149 ]. There is, therefore, an urgent clinical need for new antiviral drugs that can overcome these limitations.…”
Section: Potential Of Sls In Human Healthmentioning
confidence: 99%